Genetic diversity in saffron (Crocus sativus L.) - F A Nehvi, A M Iqbal, H Qadri, S P Singh, (Journal of Spices and Aromatic Crops, 2013)
Two hundred saffron genotypes collected from saffron growing areas of Kashmir subjected to Mahalanobis D2 analysis revealed high amount of diversity. Out of 200 genotypes, 171 genotypes were grouped in cluster I, 9 in cluster V and 7 in cluster VI whereas the other 13 clusters were monogenotypic. Maximum intracluster distance (6.50) was recorded for cluster V accommodating SH-21, SH-123, SH-200, SH-51, SH-30, SH-81, SH-69, SH-03, SH-98 genotypes collected from Kushbal, Wuyan, Khrew, Kashbal, Wulan nadh, Kruncho, Dusso, Tang and Darbagh. Maximum intercluster distance (18.14) was recorded between cluster XV and XVI showing maximum genetic divergence among the population for SH-67 collected from Chandhara and SH- 89 collected form Khrew area of Kashmir valley. Fresh stamen weight (20.86%) followed by plant height (17.77%), fresh flower weight (15.31%) and pistil length (9.98%) had contributed significantly towards diversity.